IMPLEMENTATION OF CLASSIC THEMES AND THE EXPERIENCE OF HISTORICAL VALUES IN CREATING SUSTAINABLE TOURISM SUPPORTING BUSINESSES - Haritsah Kusumaningrum; Yerika Ayu Salindri; Rosalina Nur Annisa; Juliana Juliana; Ayunindya Sandy Aulia; Agung Sulistyo (Journal of Management Small and Medium Enterprises (SMEs), 2026)
Referring to the concept of sustainability, business and tourism can be developed in line with various opportunities. The experience and uniqueness of tourism-based businesses are an added value. However, the facts show that historical tourism-based businesses have not developed much. Managers have not maximized the potential of the surrounding historical value. On the other hand, businesses based on historical nuances are considered disruptive to tourism activities, leading to concerns about damaging historical values. This study aims to investigate the management of businesses based on classical themes and historical nuances in creating sustainability. Qualitative methods were used from an interpretive perspective. Several businesses based on historical nuances and classical themes were selected as research objects, including: Cokelat Monggo (traditional-premium product), Prianti Gagarin (Classic Place), and Ndalem Natan (edu-culture business). These businesses can create sustainability through classical themes and historical nuances. The study results indicate that business managers must think intelligently when developing their businesses. Several sustainability efforts need to be implemented, such as: 1) collaboration and optimization of classical themes, 2) education and consumer experience, 3) emotional closeness, and 4) community empowerment. Keywords : Business; Sustainability; Tourism; History; Classic Themes